A systematic review of contemporary safety management research: a multi-level approach to identifying trending domains in the construction industry. Issue 2 (1st February 2023) - Newaz, Mohammad Tanvi; Ershadi, Mahmoud; Jefferies, Marcus; Pillay, Manikam; Davis, Peter
Abstract: Safety management research in construction is pervasive, therefore, a systematic review and a bibliometric mapping process that provides an overview of how recent mainstream research topics are conceptually structured is timely. Undertaking systematic mapping, contemporaneous with a scoping review of construction safety management research, can contribute to a better understanding of research outcomes and predominant topics. This study employed VOSviewer as a bibliometric tool to identify co-author citations, as well as the co-occurrence of key terms within the title, abstract and keywords of the articles. A total of 180 representative studies published in 21 peer-reviewed journals between January 2010 and November 2021 were analysed. A systematic literature review identified a significant focus on conceptualizing safety climate and safety behaviour with a growing interest in applying advanced technologies for improved safety management. Two perspectives were recognized in safety research, i.e. process-driven and people-driven, with the former focussing on accident causation while the latter on underlying the active role of workers' involvement in safety outcomes. An in-depth discussion of the findings revealed seven trending research domains: safety systems; safety skills; accident causation; safety leadership and communications; safety behaviour and attitude; safety climate and culture; and practices for improving safety performance. This review identified an emerging interest in seeking effective leadership styles and psychological interventions to promote safety culture and behaviour. In terms of practical implications, this study found opportunities to address the gap between theory and practice by adopting systems thinking and using IT for improving safety performance in construction projects.